Peradilan Anak Dilihat Dalam Pandangan John Rawls - Yustita, Widya Arum Indra; Sunardi; Hernanda, Trias (Universitas Muhammadiyah Kotabumi, 2025)
This research examines the Analysis of Juvenile Court Judges' Decisions Based on John Rawls' Perspective in Ruling on Criminal Cases of Assault Resulting in Death Committed by Minors (Case Study of Decision Number 3/Pid.Sus-Anak/2024/PN.Kds). Currently, many minors are found to be involved in criminal acts, such as violence, as reflected in Decision Number 3/Pid.Sus-Anak/2024/PN.Kds. In this case, the minor collectively engaged in violent acts, including slashing, beating, and kicking the victim, which resulted in severe injuries and ultimately led to the victim's death.This study employs a literature review method and falls under normative legal research. The data is analyzed descriptively and refers to the current doctrinal legal concepts. The research is descriptive-analytical in nature. Based on the research analysis, it can be concluded that Decision Number 3/Pid.Sus-Anak/2024/PN.Kds complies with John Rawls' principles of justice. This decision has considered the fundamental rights of the child, aimed to balance retributive and restorative justice, and provided the minor with an opportunity for rehabilitation. The minor's actions met the qualifications of the charges filed against them, and there are specific provisions in Article 170, Paragraph (2), Clause 3 of the Indonesian Criminal Code (KUHP) in conjunction with Law No. 11 of 2012 on the Juvenile Criminal Justice System, which apply exclusively to individuals committing acts of violence.